KEY PERFORMANCE INDICATORS (KPIs) IN THE QUALITY MANAGEMENT SYSTEM - Urszula Balon; Joanna M. Dziadkowiec; Magdalena Niewczas Dobrowolska (International Journal for Quality Research, 2024)
Key Performance Indicators (KPIs) are often used in business of various sizes and industries to assess operational efficiency and evaluate process effectiveness. A universal model for implementing and utilizing KPIs has been elaborated in the company, and its functionality has been verified in a selected enterprise. In accordance with the developed model, efficiency indicators have been proposed, and among them, key performance indicators (KPIs) have been selected. In addition to commonly used financial indicators, indicators evaluating the performance of the quality management system have been included, along with the need for quality cost optimization.